Incidencia y control del picudo negro (Cosmopolites sordidus) en el cultivo de plátano en el Ecuador - López Chanalata, Ángelo Luis (2020)
SUMMARY The present work of a bibliographical investigative nature, focused on the problems of the pest insect known as ¨black weevil¨ (Cosmopolites sordidus), which is of great economic importance in the agronomic management of the banana crop at the level of our country, the information compiled reveals the incidence and severity of damage caused by said pest, due to its characteristics and eating habits, weevils are hard-bodied cockroaches (belonging to the coleoptera order) that are characterized by presenting a strong beak that serves to feed and to make small holes in the speudotalls and corm of the plants that attack, the larvae or worms that cause damage by consuming the tissue, cause wounds that weaken the plant and are the gateway to pathogenic microorganisms such as the causative agents of the disease. Panama and moko, etc. Among the control methods of this insect, the literature reports several, such as: chemical, biological, cultural control, including combinations of these, making use of traps to reduce populations and thus minimize damage by reducing the threshold of economic damage of the weevil. and increase the yield of the plantain crop.